Optimization of a reliable grid-connected PV-based power plant - Rashid, Muhammad Mahbubur; Ali, Mohammad Yeakub; Hasan, Muhammad Hasibul; Mokthar, Nur Syamimi (AIP Publishing, 2023)
PV system can be considered as promising technologies in generating electrical energy. In order to meet the high demand of electric consumption much research on PV system have been done. This project focuses on maximizing the output energy from PV panel and maintain the amount of energy that has converted by a PV panel. Maximum power point tracking (MPPT) has been used in this project in optimizing the PV system. One of the methods of the MPPT technique which is Perturb and Observe (P&O) algorithm, easy to implement and has efficient performance in solving the optimization problem. The performance of P&O algorithm has been analysed through the simulation in MATLAB and experimental result.